2015
DOI: 10.1002/cne.23835
|View full text |Cite
|
Sign up to set email alerts
|

Linear correlation between the number of olfactory sensory neurons expressing a given mouse odorant receptor gene and the total volume of the corresponding glomeruli in the olfactory bulb

Abstract: Chemosensory specificity in the main olfactory system of the mouse relies on the expression of ∼1,100 odorant receptor (OR) genes across millions of olfactory sensory neurons (OSNs) in the main olfactory epithelium (MOE), and on the coalescence of OSN axons into ∼3,600 glomeruli in the olfactory bulb. A traditional approach for visualizing OSNs and their axons consists of tagging an OR gene genetically with an axonal marker that is cotranslated with the OR by virtue of an internal ribosome entry site (IRES). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 35 publications
5
75
0
Order By: Relevance
“…3B), as previously demonstrated (5). Similarly, Bressel et al recently showed a strong linear correlation between OSN number in the MOE and total glomerular volume in the OB (16). Studies demonstrating strong OSN and glomerular size correlations point toward glomerular measurements as surrogate measurements for estimating OSN number counts in transgenic mouse lines in which OR genes are genetically tagged.…”
Section: Behavioral Responses Following Olfactory Fear Acquisition Ansupporting
confidence: 60%
“…3B), as previously demonstrated (5). Similarly, Bressel et al recently showed a strong linear correlation between OSN number in the MOE and total glomerular volume in the OB (16). Studies demonstrating strong OSN and glomerular size correlations point toward glomerular measurements as surrogate measurements for estimating OSN number counts in transgenic mouse lines in which OR genes are genetically tagged.…”
Section: Behavioral Responses Following Olfactory Fear Acquisition Ansupporting
confidence: 60%
“…We found that in n5247MCZ mice at PD22, the ectopic anterior glomeruli contribute 20.0% (SD ± 6.5%) to the total glomerular volume per mouse, using methods outlined in Bressel et al (2016). It follows that ∼20% of Nrp1 – M71 + OSNs innervate these ectopic anterior glomeruli.…”
Section: Resultsmentioning
confidence: 84%
“…M71 is expressed in a few thousand OSNs at PD21 (Bressel et al, 2016). In mice that carry the gene-targeted M71-IRES-tauGFP mutation (Potter et al, 2001), M71 + OSNs express tauGFP along with M71 from bicistronic transcripts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In anesthetized rats, the CV of single OSN firing was found to be on the order of 1 (Duchamp-Viret et al, 2005). Single glomeruli receive a few thousand sensory axons although this number can vary significantly depending on receptor gene (Bressel et al, 2016). If OSNs were statistically independent of each other, the glomerular CV is expected to be on the order of 1–2%.…”
Section: Discussionmentioning
confidence: 99%